Impact of Circular Agriculture in Bangladesh: Waste-to-Value Strategies for Biogas Production and Crop Residue Management - Rana, Md. Masud M.; Ali, Md. Younus M. (Journal of Agricultural Sciences (Belgrade), 2026)
Circular agriculture (CA), derived from circular economy (CE) principles, promotes resource-efficient, closed-loop systems where organic waste is converted into renewable energy, fertilisers, and soil amendments. In Bangladesh, poor management of livestock manure, crop residues, and urban organic waste contributes to greenhouse gas emissions, soil degradation, and environmental pollution, underscoring the need for sustainable waste-to-value strategies. This review evaluates the potential of circular agriculture in Bangladesh, focusing on crop residue management and biogas production as key pathways for resource recovery and renewable energy generation. A structured literature review of 102 peer-reviewed articles and policy documents was conducted to assess current practises, technological opportunities, and policy frameworks. Waste-to-value approaches, including composting, vermicomposting, biofertilisers, biochar, and anaerobic digestion, enable conversion of agricultural residues into nutrient-rich soil amendments and renewable energy, improving soil fertility, enhancing crop productivity, and reducing reliance on chemical fertilisers. Bangladesh generates over 106 million tonnes of biomass annually, with the potential to produce more than 5 billion m³ of biogas. However, most biogas systems remain small-scale due to technological, financial, and awareness constraints. Expanding circular agriculture through integrated management of livestock manure, crop residues, and organic waste could reduce emissions, improve soil health, and strengthen rural energy security. Enhancing capacity building, technology transfer, green financing, and public–private collaboration is essential to scale up circular agriculture and support sustainable agricultural and energy systems in Bangladesh.
Keywords: waste-to-value; crop residue management; biogas production; sustainable agriculture